Обзор надродовой систематики надтрибы Micromyidi (Diptera, Cecidomyiidae) с установлением новой трибы Bryomyini - Берест, З.Л. (Вестник зоологии, 1993)
Bryomyini trib. n. is established after larval and imaginal characters. Genus Skuhraviana Mam. is transferred to the new tribe from Peromyini. Cervuatina gen. n. is established for Bryomyia cambrica E d w. (redescribed).